A user interface for terrain modelling in virtual reality using a head mounted display - Gwynn, Timothy (Department of Computer Science, 2021)
The increased commercial availability of virtual reality (VR) devices has resulted in more content being created for virtual environments (VEs). This content creation has mainly taken place using traditional desktop systems but certain applications are now integrating VR into the creation pipeline. Therefore we look at the effectiveness of creating content, specifically designing terrains, for use in immersive environments using VR technology. To do this, we develop a VR interface for terrain creation based on an existing desktop application. The interface incorporates a head-mounted display and 6 degree of freedom controllers. This allows the mapping of user controls to more natural movements compared to the abstract controls in mouse and keyboard based systems. It also means that users can view the terrain in full 3D due to the inherent stereoscopy of the VR display. The interface goes through three iterations of user centred design and testing. This results in paper and low fidelity prototypes being created before the final interface is developed. The performance of this final VR interface is then compared to the desktop interface on which it was based. We carry out user tests to assess the performance of each interface in terms of speed, accuracy and usability. From our results we find that there is no significant difference between the interfaces when it comes to accuracy but that the desktop interface is superior in terms of speed while the VR interface was rated as having higher usability. Some of the possible reasons for these results, such as users preferring the natural interactions offered by the VR interface but not having sufficient training to fully take advantage of it, are discussed. Finally, we conclude that while it was not shown that either interface is clearly superior, there is certainly room for further exploration of this research area. Recommendations for how to incorporate lessons learned during the creation of this dissertation into any further research are also made.